Identitas gender dalam lensa biologis: kajian terhadap prespektif transformasi gender ke transgender dan pemahaman fatwa ulama menurut al-qur’an. - Anwar, Hanum Salsabila (Maliki Interdisciplinary Journal, 2024)
This research discusses gender identity from a biological perspective with a focus on the transformation from gender to transgender. Involving an analysis of transgender views and interpretations of ulama fatwas based on the Koran, this research aims to understand the complexity of gender identity and its transformational impact. The research methodology involves analysis of the literature and content of the Al-Quran, with an emphasis on exploring transgender views on changing gender identity and the ulama's understanding of this phenomenon. The research results highlight how biological factors influence gender perception and transformation toward transgender status. In addition, this research tries to deepen the understanding of ulama fatwas to provide a legal and ethical context for the phenomenon of gender transformation within the framework of Islamic teachings. Thus, this research contributes to a more comprehensive understanding of gender identity from a biological perspective and a religious view.